Universities and schooling in medieval society: [essays were presented at a Conference on Universities in Medieval Society ... on September 18-20, 1997] - Courtenay, William J.; Miethke, Jürgen (Education and society in the Middle Ages and Renaissance, 2000)
The ten papers in this volume examine university and pre-university education in the 14th to 16th centuries in Germany, Italy, France, and England. Topics covered include the recruitment and support of students, studying abroad, social status, careers of graduates, university rituals, the profession of schoolmaster, and the relation of the studia to the crown.